Propuesta para mejorar la producción y rentabilidad de la finca la huerta del sector Consapamba, parroquia Amaluza, cantón Espíndola - Cordero Cordero, Elia Marina (2015)
The present research “PROPOSAL TO IMPROVE THE PRODUCTION AND PROFITABILITY OF LA FINCA LA HUERTA OF THE SECTOR CONSAPAMBA, PARISH AMALUZA, CANTON ESPINDOLA", has the following objectives: a diagnosis to find out the facts about the technical and administrative functioning of the farm. Consider improvement strategies. Define projects to improve production. Develop a proposal for improving production and profitability of the farm La Huerta. This allowed knowing the reality on the technical and administrative operation and thus being able to develop a proposal of production and profitability of the same. The methodology used was specifically the FODA analysis which allowed knowing the strengths and weaknesses, which failed to get the diagnosis of the estate and define the vision and mission, select strategies and projects and make the general programming of the plan culminating with the proposal that will improve production and profitability as it was our goal. Proposal consisting of projects and activities defined chronologically, taking into account the most priority problems by taking advantage of the opportunities as you can see in the corresponding chapters. The results achieved are as follows: the farm La Huerta has an area of 9.5 ha, of which 5 has are sown grasses and 4.5 has crops. The farm soils are loam and loam. The topography is irregular with a drop of 30%. The property has water for irrigation and watering of the animals. The climate of the sector where the estate is is temperate with an average annual temperature of 20 ° C. There are agricultural crops such as banana, plantain, corn, beans, sweet potato and vegetables; in addition, pastures. There are also species of animals such as cattle, pigs, chickens and Guinea Pigs. The main problems identified at the farm are: there is no planning in the farm. The owner has little interest in training. There is no record of the production. Accounting is not carried. The accounting of the economic movement is not and the income from the sale of some products is low. Not used technology in agricultural work, only used hand tools. There is a low production of crops with the exception of corn and beans. The existing cattle are Creole and production is low. All the productive process of crops and animals is anti-technic. The owner of the farm is not trained in the field of technical management of crops and animals both the administrative aspect. The proposal to improve the production of the farm is in the execution of the following projects and activities: implementation of the improvement Plan to the Farm. La Huerta. Training of the Administrative owner of the estate in the fields and agricultural production management. Preparation of records for the production of the farm. The basic accounting on the farm and making half-yearly balance sheets. Use of improved crop seeds. Rotation of crops among grasses and legumes to improve soil. Installation of sprinkler irrigation to make better use of water. Control of pests and diseases of crops. Improvement of the feeding of cattle with supplementary rations to nutritional needs. Preparation of health calendars forthe farm animals.